The Effect of Semi-Sitting Position on the Progress of Second Stage Labor at Jamaliah Midwifery Clinic, Pidie Regency in 2024 - Salamah Salamah; Zaitun Zaitun (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Background: The leading causes of maternal and infant mortality are complications during childbirth, such as hemorrhage and prolonged labor. The WHO recorded 69,000 cases of prolonged labor worldwide in 2020, contributing to 2.8% of maternal deaths globally and becoming a major cause of childbirth complications. The position during pushing is one of the determining factors for the success of labor. The semi-sitting position can provide comfort to the mother by helping her rest between contractions, shortening the birth canal, ensuring optimal oxygen supply from the mother to the baby, and utilizing gravity to assist in the baby's delivery process. Research Objective: To determine the effect of the semi-sitting position on the progress of second-stage labor in mothers delivering at Jamaliah Midwifery Clinic, Pidie Regency. Research Method: This research is an analytic survey with a cross-sectional approach. The population in this study consisted of all mothers delivering at Jamaliah Midwifery Clinic in November 2024, totaling 33 individuals. The research was in November 2024. Research Results: The results indicated a significant effect of the semi-sitting position on the progress of labor at Jamaliah Midwifery Clinic, Pidie Regency, in 2024, with a ρ-value of 0.009. Suggestions: Health institutions and healthcare workers, particularly midwives, are encouraged to optimize maternal care during childbirth by facilitating mothers in choosing an effective labor position to ensure a safe and comfortable delivery process. Keywords: Semi-Sitting Position, Labor Progress